A Left/Right Convergence on the New Public Management? The Unintended Power of Diverse Ideas. Issue 3 (1st October 2016) - Wennström, Johan
ABSTRACT: While it might appear self-evident that the trend toward the New Public Management (NPM) in the public administration systems of many Western countries is an outgrowth of neoliberalism, the case of Swedish education suggests that such policies can have widely different and counterintuitive sources. Ideas about education from both sides of the political spectrum appear to have paved the way for NPM in the Swedish school system. This possibility casts the ideological basis for NPM reforms in a new light, at least in the context of the Swedish school system.